Pengaruh Budaya Organisasi Dan Kepemimpinan Terhadap Komitmen Atlet Taekwondo : Studi Unit BGFC KBB - Sulaeman, Muhamad Buldan; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study investigates how organizational culture and leadership style impact the level of athlete commitment in Taekwondo unit Brave Gladiators Fighting Club (BGFC) in West Bandung Regency. All 35 people involved in this process athletes, coaches, and administrators were taken as a total sample in an associative quantitative approach. Questionnaires were used to collect data, and SPSS version 26 was used for analysis. The results showed that, partially and simultaneously, organizational culture and leadership style have a positive and significant impact on athlete commitment. It has been proven that transformational leadership and strong corporate ideals can increase athlete commitment and loyalty. This study highlights the important role played by human resource management in sports companies. Local sports clubs need to improve their organizational identity and leadership to motivate athletes to stay involved in the long term.